GC–MS profiling of Bacillus spp. metabolites with an in vitro biological activity assessment and computational analysis of their impact on epithelial glioblastoma cancer genes - Naveed, Muhammad; Ishfaq, Huda; Rehman, Shafique Ur; Javed, Aneela; Waseem, Muhammad; Makhdoom, Syeda Izma; Aziz, Tariq; Alharbi, Metab; Alshammari, Abdulrahman; Alasmari, Abdullah F. (Frontiers in Chemistry, 2023)
Background: Bacterial metabolites play a crucial role in human health and have proven effective in treating various diseases. In this study, the 16S rRNA method and streaking were employed to isolate and molecularly identify a bacterial strain, with the goal of characterizing bioactive volatile metabolites extracted using nonpolar and polar solvents. Methods: Gas chromatography–mass spectrometry (GC–MS) analysis was conducted to identify 29 compounds in the bacterial metabolites, including key compounds associated with Bacillus spp. The main compounds identified included 2-propanone, 4,4-ethylenedioxy-1-pentylamine, 1,2-benzenedicarboxylic acid, 1,1-butoxy-1-isobutoxy-butane, and 3,3-ethoxycarbonyl-5-hydroxytetrahydropyran-2-one. Results: The literature indicates the diverse biological and pharmacological applications of these compounds. Different concentrations of the metabolites from Bacillus species were tested for biological activities, revealing significant inhibitory effects on anti-diabetic activity (84.66%), anti-inflammatory activity (99%), antioxidant activity (99.8%), and anti-hemolytic activity (90%). Disc diffusion method testing also demonstrated a noteworthy inhibitory effect against tested strains. Conclusion:In silico screening revealed that 1,2-benzenedicarboxylic acid exhibited anticancer activity and promising drug-designing properties against epithelial glioblastoma cancer genes. The study highlights the potential of Bacillus spp. as a valuable target for drug research, emphasizing the significance of bacterial metabolites in the production of biological antibacterial agents.